Vrees as faktor in die regse blanke politiek in Suid-Afrika: die tweede fase van die era van volwaardige regste politieke partye, 1976-1982 - Du Bruyn, Derek; Wessels, Andre (Faculty of Humanities, University of the Free State, 2009)
The years 1976 to 1982 were traumatic for most South Africans. In June 1976, serious riots broke out in the sprawling Soweto township, and spread to other areas in the country. While some whites then, more than ever before, challenged the apartheid policy, others moved further to the right and believed that only the more rigorous application of that policy would safeguard the future of white people in the country. The National Party government clamped down on black opposition groups, individuals and the media, which in turn led to the country being isolated internationally even more than ever before. The vicious cycle of fear was fed by violence and boycotts, which led to more fear, violence and isolation, and gave impetus to the idea of a “total onslaught”. Right-wing white voters found a new (and apparently very dynamic) home in the Conservative Party, which was founded in 1982. In the meantime, the establishment of Zimbabwe under the rule of Robert Mugabe in 1980, increased external pressure on the beleaguered South African government. In this study, fear as a factor in right-wing white politics in the years 1976 to 1982 is analysed by referring to the above-mentioned and related matters.
Keywords: Soweto uprising, 1976; Soweto riots; South African government; Violence; Political parties